Filter Paper Inspired Zinc Oxide Nanomaterials with High Photocatalytic Activity for Degradation of Methylene Orange - Huang Liu; Yanhua Zhang; Hongtao Yang; Wei Xiao; Lanlan Sun (Journal of Chemistry)
Nanometer-sized zinc oxide (ZnO) has been synthesized through sol-gel method with natural cellulose substance (commercial filter paper) as template. The structure of zinc oxide nanomaterial was characterized by nitrogen adsorption-desorption and XRD. The morphology was observed by SEM and TEM. The results show that the hexagonal wurtzite phase is actually the only crystal phase in the sample and the product faithfully inherits the hierarchical morphology and the complex network structure of the original filter paper, which is composed of many randomly intersecting zinc oxide microfibers and nanosheets with lots of close stacked particles adsorbed on the surface. Moreover, these zinc oxide nanomaterials possess abundant mesoporous structure with an average pore diameter of ca. 21 nm and a wide pore size distribution (3–30 nm). Due to the strong absorption ability in the UV range, the zinc oxide nanomaterial prepared by this method displays significantly high photocatalytic activity for degrading methyl orange. In a short period of 20 minutes, the zinc oxide nanomaterial has degraded about 50% of the original MO, and the MO dye is fully degraded after UV irradiation for 80 minutes.